2018
DOI: 10.1371/journal.pone.0195824
|View full text |Cite
|
Sign up to set email alerts
|

Are men ready to use thermal male contraception? Acceptability in two French populations: New fathers and new providers

Abstract: BackgroundSince the 1970s, international research has actively pursued hormonal male contraception (HMC) and, to a lesser extent, thermal male contraception (TMC). Although the efficacy of TMC has been confirmed in limited populations, its acceptability has not been studied in either potential users or potential prescribers.MethodsA cross-sectional descriptive multicentre study of potential male users of TMC (new fathers) and potential prescribers of TMC (new providers) was conducted between November 2016 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 38 publications
5
20
0
Order By: Relevance
“…It was found, consistent with other studies conducted in SSA [39,40], that religion and religious beliefs influenced the acceptability of vasectomy. The participants referred to the Bible, claiming that it says they must reproduce and fill the earth.…”
Section: Discussionsupporting
confidence: 90%
“…It was found, consistent with other studies conducted in SSA [39,40], that religion and religious beliefs influenced the acceptability of vasectomy. The participants referred to the Bible, claiming that it says they must reproduce and fill the earth.…”
Section: Discussionsupporting
confidence: 90%
“…There are some small communities of men practising ‘do-it-yourself’ thermal treatments, either using a hot bath method or with a modified form of underwear to create ‘artificial cryptorchidism’. There is not much current active research; however, a recent French acceptability study reported that one-third of respondents showed interest in this method as a contraceptive 28…”
Section: Non-hormonal Approaches Acting On Spermatogenesismentioning
confidence: 99%
“…1 ). Of these, we included 41 articles reporting on values and preferences around contraceptive methods from the perspective of health workers in this review ( Table 1 ) [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] . The 41 articles capture values and preferences of 12,643 health workers from 27 countries.…”
Section: Resultsmentioning
confidence: 99%
“…However, one cross-sectional study noted that other health workers counseled on IUDs and considered the method safe [38] . Male methods such as vasectomy were explicitly mentioned in 2 studies from France and the United States: in general, male methods were not counseled on as often as contraceptive methods for females, and when compared to female sterilization, male sterilization was counseled on less frequently, though 57% of Fellowship in Family Planning (Ob/Gyn and family medicine physician trainee) respondents in the US reported that vasectomy was their preferred method of sterilization [ 19 , 43 ].…”
Section: Resultsmentioning
confidence: 99%